MARKETING AND COMPETITIVE ADVANTAGE IN THE STUDENTS OF THE FCA - UNMSM (PERU), COMPARED WITH THE STUDENTS OF MANAGEMENT OF THE UNIVERSITY OF BERGAMO (ITALY) - Mayurí Barrón, Jorge (2015)
The research focuses on a comparative study of the use of the Personal Marketing tool and competitive advantage generated by this tool between students of the Academic School of Management, Academic School of International Business and Academic School of Tourism of the Faculty of Business Administration of the Major National University of San Marcos in Peru and students of the Department of Management at the University of Bergamo in Italy, this survey was conducted to students of both universities determining that the students of the University of Bergamo use best marketing staff and therefore generating a better personal competitive advantage over students from the University of Peru, the type of study not experimental, cross-section at one time for each university